Polygynous family structure and child undernutrition in Africa: Empirical evidence from Nigeria - Amare, Mulubrhan; Mahrt, Kristi; Mavrotas, George; Arndt, Channing (African Association of Agricultural Economists, 2019)
A growing interest is emerging in the literature to explore how child nutrition is affected by sociocultural practices, such as polygyny. However, evaluation of the effect of polygyny on child nutrition has been hindered by the complexity of the relationship. This paper investigates the impact of polygyny on anthropometric outcomes recognizing that unobservable household characteristics may simultaneously influence both the polygyny decision and the ability to adequately nourish children. We apply an instrumental variable approach based on the occurrence of same sex siblings in a woman’s first two births to generate exogenous variation in polygyny. Using 2008 and 2013 Nigeria Demographic and Health Survey data, we find that same sex siblings predict polygyny. We also find a strong positive effect of polygyny confirming its detrimental effect on both long-term and short-term child undernutrition, with a greater impact in poorer and more urban households.